Analisis Isi Pesan Dakwah dalam Film “Buya Hamka” Karya Fajar Bustomi - Fadilah, Nurhikmah; Abdullah , Abdullah (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Raden Fatah Palembang, 2024)
The rapid development of technology and communication will affect how a da'i conveys the message of da'wah to mad'u. Da'i can deliver da'wah through various available media; using this media is an effective strategy to attract the attention of mad'u, and the reach of da'wah becomes wider. When da'i deliver da'wah by using the media, the delivery of da'wah messages can be presented interestingly and diversely, thus keeping away the risk of boredom. The method that has proven effective in delivering da'wah messages is through film media. Through scenes, sounds, and images, da'wah messages can be conveyed strongly and clearly, making it easy for mad'u to understand. This study aims to identify the da'wah message in the film “Buya Hamka .